EDUCATIONAL VALUES OF AMTSÂL VERSES IN AL QURAN SURAH AL-BAQARAH (COMPARATIVE STUDY OF TAFSIR BY M. QURAISH SHIHAB AND ANWAR AL-BAZ) - Jannah, Hidayatul; Noor, Fatwiah; Ramli, M; Ardi, Sahibul (Proceeding of International Conference on Islamic Education (ICIED); Vol 8 No 1 (2023): Proceeding of International Conference on Islamic Education (ICIED), 2023)
Education is a lifelong endeavor that is pursued by every individual as either a learner or an educator. Education is the most influential thing in shaping a human's character. This is reflected in how the education he has gone through and how it has a great impact on someone's life.  Education is a process of instilling values that will shape human personality. Islamic education has the main basis, namely the Qur'an as the main source of value which is absolute and universal.  The Qur'an as a source of education conveys its message in two ways, namely explicitly and implicitly. Therefore, things that are implied need to be studied further in order to convey the intent of the message. This study analyzes the educational values that are presented in the verses of amstal in QS. Al Baqarah through the interpretation of M. Quraisy Shihab and Anwar Al-Baz. The selection of these two mufassirs is inseparable from their ways and methods in understanding the content of the verses of the proverbs.